Pentingnya Pariwisata Berkelanjutan dalam Menjaga Keseimbangan Lingkungan - Saputra, I Putu David Adi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The purpose of writing this work is to determine the importance of sustainable tourism in maintaining environmental balance. This research uses literature review methods and interviews with stakeholders to explore the role of sustainable tourism in maintaining environmental balance. Data is analyzed qualitatively with a focus on the contribution of sustainable tourism, presented through narratives, tables and graphs to provide a holistic understanding. The results of this work are that sustainable tourism provides economic and social benefits, but integration with the environment is important to avoid negative impacts. Key factors such as Attraction, Accessibility, Amenities and Ancillary (4A) play a vital role in the development of tourism destinations. Although revitalization of tourist attractions improves local economies, transformation to sustainable tourism requires collaboration and environmental conservation. The contribution of the private sector is crucial, in line with the government's vision of making tourism a regional characteristic. In Indonesia, tourism is considered a catalyst for economic growth and community prosperity, with a focus on comprehensive policies and compliance with regulations. The Sustainable Tourism Development Concept emphasizes the sustainability of natural resource management and the role of the private sector, with ongoing efforts for strong tourism destinations. Environmental sustainability is the main focus, emphasized by the government's role in achieving sustainable tourism goals that pay attention to ecological and social aspects.